Health Care Spending Issues in Advanced Economies - Jenkner, Eva.; Leive, Adam. (Washington, D.C. : International Monetary Fund, 2010)
This technical note analyzes the health care spending issues in advanced economies. Both public and total health spending have increased substantially in advanced countries. Total health spending increased by more than 6 percentage points of GDP in the Organization for Economic Cooperation and Development countries between 1970 and 2007. This note examines the recent trends in health care spending in advanced countries. It discusses the main challenges for advanced countries over the medium term. Policy options for containing health care costs are also described.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet